2008
DOI: 10.1002/uog.6121
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal sonographic and MRI findings in a pregnancy complicated by uterine sacculation: case report and review of the literature

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 16 publications
0
54
0
1
Order By: Relevance
“…9 Cases of maternal and foetal death have also been described. 10,11 The incidence of incarcerated uterus has been quoted to be around 1 in 3000 to 10,000 cases. 12 In the authors' institution where electronic medical record has been used over period of 5 years involving more than 60,000 deliveries, this is the first case ever recorded.…”
Section: Discussionmentioning
confidence: 99%
“…9 Cases of maternal and foetal death have also been described. 10,11 The incidence of incarcerated uterus has been quoted to be around 1 in 3000 to 10,000 cases. 12 In the authors' institution where electronic medical record has been used over period of 5 years involving more than 60,000 deliveries, this is the first case ever recorded.…”
Section: Discussionmentioning
confidence: 99%
“…This was also true in the first pregnancy of our patient. When the cervix is elongated and wedged behind the symphysis, abdominal sonography is superior to transvaginal sonography in revealing the position of the cervix and its internal ostium and defining the relationships between the bladder, uterus and vagina [19]. Magnetic Resonance Imaging (MRI) appears to be the imaging method of choice [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic Resonance Imaging (MRI) appears to be the imaging method of choice [20,21]. Characteristic MRIfindings of a posterior incarceration is a "free-standing", T-shaped multi-layer myometrium on sagittal images and a small cleft-like cystic lesion between the bladder and the sacculation on axial images, corresponding to the stretched cervix and the caudal part of the uterus [10,19,20,21]. This is illustrated in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few reports have indicated that a uterine rupture can occur in primigravida, although this is extremely rare [2,3], with etiological or risk factors including a history of uterine surgery, labor augmentation or underlying connective tissue disease [2-4]. A thin uterine wall, as a result of uterine sacculation [5,6] or uterine diverticulum [7], may also induce uterine rupture.…”
Section: Introductionmentioning
confidence: 99%